Analisis Kebutuhan Pelatihan Arsiparis Berbasis Competency-Based Training (CBT) di Universitas Negeri Yogyakarta - Putri, Adhitya Eka; Astuti, Yuni (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
This study aims to analyze the training needs to support the skills and knowledge of archivists in managing records and archives at Universitas Negeri Yogyakarta (UNY). The research method used is a qualitative approach with interview techniques with five archivists. The results of the study indicate that limited skills in digitalization and management of electronic records and archives, lack of human resources, and minimal digital infrastructure are the main obstacles in the recordkeeping and archiving system. In addition, there is still a gap between the skills possessed by archivists and the demands of technological developments and archival policies. This study recommends improving the competence of archivists through ongoing training that includes digital skills, electronic records and archives management, archives conservation, and understanding of archival regulations. In addition, investment in technological infrastructure and institutional policy support are needed to improve the effectiveness of the archival system at UNY. The implications of this study highlight the importance of technology integration in the management of academic archives and the strategic role of archivists in maintaining the sustainability of institutional information. The results of the study can be the basis for the development of training programs and policies that are more adaptive to the challenges of the digital era.